Stress Is Associated with Quality of Life Reduction among Health Professionals in Vietnam: A Multisite Survey - Le Thi Kieu Hanh; Ngo Van Toan; Vu Minh Hai (Mental Illness)
Stress in healthcare workers is increasingly common in recent times. Stress can have negative effects on the mental health and quality of life of healthcare workers. This study is aimed at measuring the quality of life and determining the relationship between quality of life and stress of health professionals in some hospitals in Vietnam. A cross-sectional descriptive study was conducted on 520 health professionals working at Hanoi Medical University Hospital and Thai Binh Medical University Hospital. The World Health Organization Quality-of-Life Scale (WHOQOL-BREF) and the Depression, Anxiety, and Stress Scale-21 Items (DASS-21) scale were used to assess the quality of life and the stress status of healthcare workers. Multivariate regression was performed to measure the relationships between stress and quality of life. Results showed that the level of stress of health workers according to the DASS-21 scale at mild, moderate, severe, and very severe was 10.7%, 8.7%, 5.6%, and 2.9%, respectively. The mean score of overall quality of life was 60.97±11.39. Health workers under stress had a decrease in quality of life scores in physical, mental, social, and environmental domains. Stressed health workers had a reduced quality of life. Attention should be paid to providing appropriate interventions to reduce stress and improve the quality of life in healthcare workers.